2003
DOI: 10.1074/jbc.m310047200
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1-mediated Vascular Permeability Factor/Vascular Endothelial Growth Factor-dependent Endothelial Cell Migration

Abstract: Neuropilin-1 (NRP-1) has been found to be expressed by endothelial cells and tumor cells as an isoform-specific receptor for vascular permeability factor/vascular endothelial growth factor (VEGF). Previous studies were mainly focused on the extracellular domain of NRP-1 that can bind to VEGF 165 and, thus, enables NRP-1 to act as a co-receptor for VEGF 165 , which enhances its binding to VEGFR-2 and its bioactivity. However, the exact functional roles and related signaling mechanisms of NRP-1 in angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 40 publications
7
181
2
Order By: Relevance
“…Neuropilin-1 has also been implicated in chemotaxis of breast cancer cell lines through autocrine pathways involving both VEGF and SEMA3a by complexing with plexin-A1 (Bachelder et al, 2003). Interestingly, whereas the short 40 aminoacid intracellular domain had previously been thought to be incapable of independent signalling, one study utilising chimeric NRP-1 suggests that the intracellular domain of NRP-1 alone may mediate VEGF-dependent migration in endothelial cells (Wang et al, 2003). Thus, the mechanisms by which NRP-1 induces functional changes in tumour cells require further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropilin-1 has also been implicated in chemotaxis of breast cancer cell lines through autocrine pathways involving both VEGF and SEMA3a by complexing with plexin-A1 (Bachelder et al, 2003). Interestingly, whereas the short 40 aminoacid intracellular domain had previously been thought to be incapable of independent signalling, one study utilising chimeric NRP-1 suggests that the intracellular domain of NRP-1 alone may mediate VEGF-dependent migration in endothelial cells (Wang et al, 2003). Thus, the mechanisms by which NRP-1 induces functional changes in tumour cells require further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…It also is reported that G q/11 and G␤␥-mediated pathways are required for human umbilical vein endothelial cell (HUVEC) cell migration stimulated by vascular endothelial growth factor (VEGF). 48 G-protein coupling for chemotaxis also may be cell-type dependent. For example, S1P and LPA-induced chemotaxis is resistant to PTX in T-helper 1 cells, 23 while it is sensitive to PTX in many other cell types.…”
Section: G I -Independent Pathways In Cell Migrationmentioning
confidence: 99%
“…VEGF binding to neuropilin-1 and neuropilin -2 leads to increased endothelial mitogenesis and chemotaxis. 27,28 The VEGF family comprises 6 glycoproteins; VEGF-A, VEGF-B, VEGF-C, VEGF-D, VEGF-E, and placental growth factor. Within these major VEGF subtypes are multiple isoforms.…”
Section: Molecular Interactions With Vegfmentioning
confidence: 99%